Rozłóż wielomian na czynniki:
a) [tex]w(x) = (2x - 1)^{4} - x^{2}[/tex]
b) [tex]w(x) = (x-2)^{4} - (2x+1)^{4}[/tex]



Odpowiedź :

Odpowiedź:

a)    ... = [ ( 2 x - 1)² - x]*[ ( 2 x - 1)² + x ] = [4x²- 4x - 1 - x]*[ 4 x² - 4 x + 1 + x ] =

           = ( 4 x² - 5 x - 1)*( 4 x²-3 x + 1 ) =

          = 4*(x - [tex]\frac{5 - \sqrt{41} }{8})*( x - \frac{5 + \sqrt{41} }{8}[/tex]) *( 4 x² - 3 x + 1)

=================================================

bo

Δ[tex]_1 = 25 - 4*4*(-1) = 25 + 16 = 41[/tex]

√Δ[tex]_1 = \sqrt{41}[/tex]

[tex]x_1 = \frac{5 - \sqrt{41} }{8}[/tex]       [tex]x_2 =[/tex] [tex]\frac{5 + \sqrt{41} }{8}[/tex]

Δ[tex]_2 = 9 - 4*4*1 = 9 - 16 < 0[/tex]  - brak miejsc zerowych

----------------------------------------------------------------------------------

b)       ... = [ (x - 2)² - (2 x + 1)²]*[ (x - 2)² + ( 2 x + 1)²] =

=  [ x²- 4 x + 4 - 4 x²-4 x - 1 ]*[ x² - 4 x + 4 + 4 x² + 4 x + 1 ] =

=  [ -3 x² - 8 x + 3 ]* [ 5 x² + 5 ] = -3*( x - [tex]\frac{1}{3}[/tex] )*( x + 3)* 5*( x² + 1) =

= - 15*( x - [tex]\frac{1}{3}[/tex] )*( x + 3)*( x² + 1 )

===========================

bo         Δ = (-8)² - 4*(-3)*3 = 64 + 36 = 100            √Δ  = 10

[tex]x_1 = \frac{8 - 10}{- 6} = \frac{1}{3}[/tex]                      [tex]x_2 = \frac{8 + 10}{- 6} = - 3[/tex]

Szczegółowe wyjaśnienie: